2023
DOI: 10.4254/wjh.v15.i6.755
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of liver fibrosis: Past, current, and future

Abstract: Liver fibrosis accompanies the progression of chronic liver diseases independent of etiologies, such as hepatitis viral infection, alcohol consumption, and metabolic-associated fatty liver disease. It is commonly associated with liver injury, inflammation, and cell death. Liver fibrosis is characterized by abnormal accumulation of extracellular matrix components that are expressed by liver myofibroblasts such as collagens and alpha-smooth actin proteins. Activated hepatic stellate cells contribute to the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 147 publications
0
7
0
Order By: Relevance
“…Many antifibrotic treatments targeting various fibrotic pathways have been assessed in liver fibrosis, such as angiotensinconverting enzyme inhibitors, angiotensin receptor blockers, interferon, pioglitazone, colchicine, farglitazar, simtuzumab, non-coding RNAs, pegbelfermin, natural herbs, and transplantation of stem cells (Friedman, 2015;Rockey et al, 2015;Trautwein et al, 2015). Unfortunately, only a very few of these treatments show modest effects in clinical trials, whereas most other treatments are ineffective (Friedman, 2015;Malaguarnera et al, 2015;Rockey et al, 2015;Trautwein et al, 2015;Zhang et al, 2023). The lack of broadly effective treatment for fibrosis continues to fuel the search for new molecular targets of fibrosis and effective drugs for prevention and therapy.…”
Section: Lp340 Protects Against Hepatic Fibrosis In Vivomentioning
confidence: 99%
See 2 more Smart Citations
“…Many antifibrotic treatments targeting various fibrotic pathways have been assessed in liver fibrosis, such as angiotensinconverting enzyme inhibitors, angiotensin receptor blockers, interferon, pioglitazone, colchicine, farglitazar, simtuzumab, non-coding RNAs, pegbelfermin, natural herbs, and transplantation of stem cells (Friedman, 2015;Rockey et al, 2015;Trautwein et al, 2015). Unfortunately, only a very few of these treatments show modest effects in clinical trials, whereas most other treatments are ineffective (Friedman, 2015;Malaguarnera et al, 2015;Rockey et al, 2015;Trautwein et al, 2015;Zhang et al, 2023). The lack of broadly effective treatment for fibrosis continues to fuel the search for new molecular targets of fibrosis and effective drugs for prevention and therapy.…”
Section: Lp340 Protects Against Hepatic Fibrosis In Vivomentioning
confidence: 99%
“…Liver fibrosis results from wound-healing responses to repeated injury during the progression of most chronic liver diseases (Bataller and Brenner, 2005;Zhang et al, 2023). Many cellular and molecular signals contribute to the initiation and progression of liver fibrosis, including cell death, oxidative stress, mitochondrial dysfunction, inflammatory processes, proinflammatory/profibrotic cytokines, vasoactive substances, adipokines, microRNAs, ductular reactions, and genetic factors (Gabele et al, 2003;Bataller and Brenner, 2005;Zhang et al, 2023).…”
Section: Lp340 Decreases Oxidative Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, multiple drugs have been tested for their potential anti-inflammatory, cytoprotective, and antifibrotic effects in NAFLD patients [3,173,174]. Unfortunately, a great number of them have failed to demonstrate histologic improvement in fibrosis in clinical trials, but a few have shown some promising benefits [174][175][176]. However, there is no drug approved so far for NASH-associated fibrosis in patients with or without T2DM.…”
Section: Factors Associated With Fibrosis Progression and Regressionmentioning
confidence: 99%
“…According to the authors, antifibrotic treatment should include behavioral therapy, medications, and nutritional factors. Introducing such a procedure may be helpful in reducing inflammation and oxidative stress and preventing the death of hepatocytes, which may significantly reduce the risk of fibrosis and organ failure [7].…”
Section: Introductionmentioning
confidence: 99%